PENGEMBANGAN MULTIMEDIA PEMBELAJARAN BERBASIS KOMPUTER MODEL PERMAINAN PADA MATA PELAJARAN EKONOMI DI SMA MUHAMMADIYAH 1 PALEMBANG - Ade Irma Suryani; M. Djahir Basir; Rusmin AR (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2014)
This research is research development that aims to produce a multimedia computer-based learning model is a valid game, practical, and to know the effectiveness of the use of multimedia generatedresults student learning. The model used is the development model of Rowntree which consists of three stages, namely the planning phase, the development phase and the phase of evaluation that have been modified with a formative evaluation Tessmer. To view the validity, researchers using sheets of validation performed on the stage of the assessment of the experts with the results averaged – averaged assessment 78% of media experts with a Good category and averaged – averaged expert assessment material of 92% with Excellent category . To see the practicalities, performed on the stage of test one results through interviews with a percentage of 85% and a small group using a detailed questionnaire sheet with the median results – averages 90% of student responses by category. As for seeing the effectiveness of performed on stage with a test using the test results of the study early (Pre – test) and tests the results of the study end (Posttest). Field Test in this research was conducted in the laboratory of Computer2 SMA Muhammadiyah Palembang with 1 number of students as many as 26 people and percentage complete value enhancement resultsof 53.9% and the total average – average value of the mastery of 88.5% has passing criteria of classical criteria of 85%, so the use of the resulting categories include Multimedia effectively. The results showed that the multimedia computer-based learning model the resulting game was valid, practical and effective on Economic subjects and can be used as an alternative in the learning process